The investigation of stability on slopes utilizing reinforcement gabion walls and concrete piles for mitigating landslide disasters - Chairullah, Banta; Sungkar, Munira; Munirwan, Reza Pahlevi; Jamaluddin, Khaizal; Ramadhani, Ferda Febrian; Putra Jaya, Ramadhansyah (Bentham Science Publishers B.V., 2024)
Introduction: Landslides frequently occur along roads crossing mountainous terrain during the rainy season, posing a significant risk of severe disruption to land transportation routes. Efficient and accurate resolutions are essential in managing landslides to facilitate immediate transportation recovery, such as gabion walls and pile installation. Aim: This article aimed to evaluate the effect of installing gabions and piles for safety measures on the stability of slope landslides. The analysis of slope stability was performed utilizing the Plaxis 2D software. For reinforced slopes, the Safety Factor (SF) value utilized as a benchmark for evaluating slope stability was SF ≥ 1.5. Methods: An assessment of the stability of the slope was conducted under three conditions: its original state, after reinforcement with gabions, and after the integration of gabions with mini piles. The dimensions of the gabion setting, as determined by the L-W-H notation (length-width- height), were 2 m x 1m x 0.5 m and 1 m x 2 m x 0.5 m. The pile was designed to be 2.5 m long at the gabion's end. The analysis was conducted at 45°, 60°, 70°, and 90° slopes. Results: Based on the results of slope stability calculations, an SF = 1.11 was determined under no reinforcement conditions. By applying reinforced gabion walls measuring 2 m in width combined with mini piles at a 45° slope, the best SF was achieved, which was 2.58. Conclusion: Given the comparable topographical circumstances, it is expected that the outcomes of this analysis on slope stability will be applicable in mitigating the occurrence of landslides.